Inventory of the Orchidaceae Family in Jorong Harapan Tinggam Community Forest Talamau Pasaman Barat District West Sumatera - Elza Safitri; Zikra Zikra; Syahmitul Rafita; Abizar Abizar (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2023)
Tinggam Community Forest is a highland tropical forest area in which many types of orchids are found. Orchids generally live as epiphytes, but there are also terrestrial ones. The purpose of this study was to determine the types of natural orchids found in the forest in the Jorong Harapan Tinggam Community Forest, Talamau District, West Pasaman Regency West Sumatera. The research method used is a descriptive survey using a roaming technique by tracing the forest from the outskirts to the forest as a whole. From the results of the study, it was found that there were 16 species, consisting of 13 epiphyte orchids, while the terrestrial orchids obtained were 3 species. The orchid species obtained were: Agrostophyllum lampongense Blume., Arundina graminifolia Hochr., Bulbophyllum sp., Bulbophyllum angustifolium Lindl., Bulbophyllum plavescens Blume., Coelogyne rochussenii Vriese., Cymbidium Rchb.fcrumenatum spp . dayanum De., Eria iridifolia Hook.F., Eria pilifera Ridley., Grammathophyllum speciosum Blume., Phaius tankervilleae Blume. Robiquatia spatulata Blume., Spathoglottis plicata Roxb., Thelasis carinata Blume. It can be concluded that the Jorong Harapan area is an ideal habitat for orchid growth.